AFGHANISTAN: A NEW PAGE IN THE STUDY - Anri Sharapov (Web of Journals Publishing, 2023)
It is known that at the moment, the importance of Afghanistan is urgent both on the global and the regional scale. The issue of Afghanistan for Central Asia is not only on the permanent agenda of the governments of the region, but also an urgent issue for the international community in terms of ensuring security and promoting cooperation. From this point of view, the study of socio-political processes in Afghanistan has scientific and practical importance. “Afghanistan. Dictionary-reference" prepared by Professor I.I.Bobokulov satisfies the scientific needs of researchers in the field of international relations and Afghan studies.
Keywords: Afghanistan, Central Asia, geopolitical situation, sustainable development, regional security.